The Integration of Value Education and Islamic Religious Education within the Framework of National Education - Ahmad Novta Sebad Linaci; Ade Erlangga; Desiana Desiana; Dimas Al Ghifari; Syaiful Anwar; Chairul Anwar (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
Integration can refer to the combination of different elements into one larger whole, whether in the social, cultural, economic or educational fields. Integration in values ​​education refers to the process of combining and integrating certain values ​​into the curriculum and overall educational practice. The integration of values ​​education and Islamic Religious Education (PAI) is an approach that combines values ​​which include moral, ethical and aesthetic aspects which are the basis for a person's actions and attitudes and is combined with Islamic religious education delivered in the teaching and learning process. The National Education Framework in Indonesia itself is a system designed to regulate and manage education as a whole, covering various aspects aimed at making the nation's life more intelligent. The National Education Framework is the structure and guidelines that regulate the pathways, levels and types of education in Indonesia, in accordance with Law no. 20 of 2003 concerning the National Education System. This framework aims to create an education system that is integrated, high quality and relevant to society's needs and current developments.